Public awareness of cancer in Britain: a population-based survey of adults - Robb, K (Nature Publishing Group, 2009)
OBJECTIVE: To assess public awareness of cancer warning signs, anticipated delay and perceived barriers to seeking medical advice in the British population. METHODS: We carried out a population-based survey using face-to-face, computer-assisted interviews to administer the cancer awareness measure (CAM), a newly developed, validated measure of cancer awareness. The sample included 2216 adults (970 males and 1246 females) recruited as part of the Office for National Statistics Opinions Survey using stratified probability sampling. RESULTS: Awareness of cancer warning signs was low when open-ended (recall) questions were used and higher with closed (recognition) questions; but on either measure, awareness was lower in those who were male, younger, and from lower socio-economic status (SES) groups or ethnic minorities. The most commonly endorsed barriers to help seeking were difficulty making an appointment, worry about wasting the doctor's time and worry about what would be found. Emotional barriers were more prominent in lower SES groups and practical barriers (e.g. too busy) more prominent in higher SES groups. Anticipated delay was lower in ethnic minority and lower SES groups. In multivariate analysis, higher symptom awareness was associated with lower anticipated delay, and more barriers with greater anticipated delay. CONCLUSIONS: A combination of public education about symptoms and empowerment to seek medical advice, as well as support at primary care level, could enhance early presentation and improve cancer outcomes.